2013
DOI: 10.2344/0003-3006-60.2.46
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Cortisol, Salivary Alpha Amylase, and the Dental Anxiety Scale

Abstract: The aim of this study was to investigate the correlation between dental anxiety, salivary cortisol, and salivary alpha amylase (sAA) levels. Furthermore, the aim was to look into individual differences such as age, race, gender, any existing pain, or traumatic dental experience and their effect on dental anxiety. This study followed a cross-sectional design and included a convenience sample of 46. Every patient was asked to complete the Dental Anxiety Scale (DAS) and a basic demographic/dental history question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 36 publications
5
51
2
3
Order By: Relevance
“…In the same study that utilized a corneal transplant surgery video as stressful process, similar results to the results of the present study were obtained (17). In the study by Sadi et al, increase of SAA in patients undergoing routine dental examinations was not observed (1). Various reasons can justify this lack of correlation in the study by Sadi because in this study, saliva samples were taken only once and before examining patients, and the patients had no history of dental treatment and dental pain.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In the same study that utilized a corneal transplant surgery video as stressful process, similar results to the results of the present study were obtained (17). In the study by Sadi et al, increase of SAA in patients undergoing routine dental examinations was not observed (1). Various reasons can justify this lack of correlation in the study by Sadi because in this study, saliva samples were taken only once and before examining patients, and the patients had no history of dental treatment and dental pain.…”
Section: Discussionsupporting
confidence: 79%
“…STAI is a standard questionnaire that measures general anxiety) (17). However, Sadi et al did not find any correlation between scores of the Corah's DAS and SAA questionnaires (1). This lack of relationship may be due to sampling saliva in a non-stressful situation and lack of dental pain history of the participants under study.…”
Section: Iranmentioning
confidence: 79%
See 2 more Smart Citations
“…Dental anxiety is a common phenomenon which affects the process of delivering proper dental care to society in almost all age ranges [1,2]. The causes of this problem vary from lack of knowledge to environmental perception.…”
Section: Introductionmentioning
confidence: 99%